GATA transcription factors integrate Wnt signalling during heart development. - Afouda, B; Martin, J; Liu, F; Ciau-Uitz, A; Patient, R; Hoppler, S (2008)
Cardiogenesis is inhibited by canonical Wnt/beta-catenin signalling and stimulated by non-canonical Wnt11/JNK signalling, but how these two signalling pathways crosstalk is currently unknown. Here, we show that Wnt/beta-catenin signalling restricts cardiogenesis via inhibition of GATA gene expression, as experimentally reinstating GATA function overrides beta-catenin-mediated inhibition and restores cardiogenesis. Furthermore, we show that GATA transcription factors in turn directly regulate Wnt11 gene expression, and that Wnt11 is required to a significant degree for mediating the cardiogenesis-promoting function of GATA transcription factors. These results demonstrate that GATA factors occupy a central position between canonical and non-canonical Wnt signalling in regulating heart muscle formation.